The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4236/jbise.2017.1011040
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocytes Derived from Human Induced Pluripotent Stem Cells: An In-Vitro Model to Predict Cardiac Effects of Drugs

Abstract: Introduction: Cardiomyocytes derived from human induced pluripotent stem cells (hiPSC-CM) form spontaneously beating syncytia in-vitro. We evaluated whether hiPSC-CM are a compelling model of human cardiac pharmacology useful for early drug development. Methods: We measured hiPSC-CM beating frequency using Ca-sensitive dyes and a high-throughput screening system. We quantified the effects of 640 drugs with various structures and pharmacologies. Results: When tested at 1 µM, most drugs without direct effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 84 publications
(98 reference statements)
0
15
1
Order By: Relevance
“…In a validation study performed with many drugs approved for human use, we showed that the assay reacts to drugs used in human medicine as predicted by existing clinical data 5 . Because this method considers all potential effects on cardiac rhythm, it complements the Comprehensive in vitro Proarrhythmic assay (CiPA) initiative 14 that specifically assesses pro-arrhythmic potential.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In a validation study performed with many drugs approved for human use, we showed that the assay reacts to drugs used in human medicine as predicted by existing clinical data 5 . Because this method considers all potential effects on cardiac rhythm, it complements the Comprehensive in vitro Proarrhythmic assay (CiPA) initiative 14 that specifically assesses pro-arrhythmic potential.…”
Section: Discussionmentioning
confidence: 86%
“…Blockers of cardiac ion channels affect the rhythm of the cardiomyocytes in a reproducible manner 5 . Amlodipine, a blocker of the slow Ca channels 9 , accelerates the rhythm more than 100% in a concentration-dependent manner up to 1 µM ( Figure 2A ).…”
Section: Representative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We updated network parameters ( +1 ) using adaptive momentum estimation (ADAM) optimization algorithm [79] based on the average gradient of overall loss function with respect to the network parameters for 64 randomly selected simulated AP traces (mini-batch = 64) at each training iteration (Eqs. [13][14][15].…”
Section: Long-short Term Memory (Lstm) Layers (Figure 3d)mentioning
confidence: 99%
“…While in vitro iPSC-CM utilization allows for observation of a variety of responses to drugs and other perturbations [9][10][11][12], there is still a major inherent limitation: The complex differentiation process to create iPSC-CMs results in a model of cardiac electrical behavior, which is relatively immature, resembling fetal cardiomyocytes. Hallmarks of the immature phenotype include spontaneous beating, immature calcium handling, presence of developmental currents, and significant differences in the relative contributions of repolarizing potassium currents compared to adult ventricular myocyte [13][14][15].…”
Section: Introductionmentioning
confidence: 99%